2012
DOI: 10.1097/sla.0b013e31824f68b2
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy for Non-Melanoma Head and Neck Cancers

Abstract: In accordance with the clinical results shown, we encourage further investigation to establish ECT's use as first line treatment especially in basocellular carcinomas of the head and neck area and for squamocellular carcinomas of the lip with no detectable cervical lymphoadenopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 25 publications
3
69
0
1
Order By: Relevance
“…Another recent review and clinical study (71) suggested that the SOP may need refinement, as the current SOP for ECT may not be suitable for tumors bigger than 3 cm in diameter, which require multiple, consecutive ECT treatments. Several ongoing ECT studies are targeting superficial tumors, predominantly melanoma but also chest wall breast cancer recurrences (72)(73)(74) and head and neck cancers (75). Furthermore, the technology is also being adapted for the treatment of deep-seated tumors, such as colorectal tumors; soft tissue sarcomas; and brain, bone, and liver metastases (45,52).…”
Section: Electrochemotherapymentioning
confidence: 99%
“…Another recent review and clinical study (71) suggested that the SOP may need refinement, as the current SOP for ECT may not be suitable for tumors bigger than 3 cm in diameter, which require multiple, consecutive ECT treatments. Several ongoing ECT studies are targeting superficial tumors, predominantly melanoma but also chest wall breast cancer recurrences (72)(73)(74) and head and neck cancers (75). Furthermore, the technology is also being adapted for the treatment of deep-seated tumors, such as colorectal tumors; soft tissue sarcomas; and brain, bone, and liver metastases (45,52).…”
Section: Electrochemotherapymentioning
confidence: 99%
“…Because of the clinically present nodus it sometimes misleads in terms of the evaluation of the excision width (therefore a high percentage of the presence of tumor at the resection edge) [17][18][19][20][21][22][23][24] . But with this kind, there is no clear visual limits of tumor from healthy skin which requires, depending on the size, at least 5 mm excision into the healthy tissue.…”
Section: Discussionmentioning
confidence: 99%
“…An OR was obtained in all cases 6 weeks after ECT: 18 (72%) patients had a CR, while a partial response was observed in 7 cases (28%), according to the WHO criteria. At the 18-month follow-up, all the patients with CR were still disease-free and those patients with partial response showed stable disease (35).…”
Section: Head and Neck Tumorsmentioning
confidence: 92%
“…However, these results need further verification. Another study, conducted by researchers from Cardarelli Hospital in Naples, Italy, evaluated the effectiveness of ECT in the treatment of patients with nonmelanoma cutaneous head and neck tumors (35). All cancers were classified according to the histologically confirmed diagnosis, the site, the size, and TNM staging.…”
Section: Head and Neck Tumorsmentioning
confidence: 99%